Pemberdayaan Perempuan melalui Pelatihan Pembuatan Jelly Art Pudding di Kelurahan 30 Ilir Palembang - Herda Sabriyah Dara Kospa (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Covid-19 Pandemic and global crisis have caused tremendous impact to the increase of unemployment and higher price for food and fuel in Kelurahan 30 Ilir Palembang. Therefore, the role of women, especially housewives, is pivotal in enhancing household income to be financially independent. This community service aimed to provide entrepreneurial skills for housewives in Kelurahan 30 Ilir through jelly-based pudding creations or jelly art pudding. Besides its low price and easy access, the use of artful jelly can increase the added-value of the products. Through this training, targeted community was encouraged and inspired to be an entrepreneur and to explore this culinary art. During this activity, all of participants technically trained how to make jelly art, as well as how to calculate profit and loss in selling process. The activity outcome showed all participants actively participated and created a small group who enthusiastically desired to develop this art culinary as one of solution in improving family income.